Measuring Work and Environmental Culture as Part of the Internal CSR (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Corporate social responsibility is an approach that supports sustainable business operations. Among the elements of the CSR concept (leadership, employees, environment, society, product and service) inward activities are examined in the present study based on the aspects of employee safety and working environment. Examining environmental and occupational safety culture helps the leadership to uncover the areas to be developed in strategy planning. Employee satisfaction, safety and the adequate working conditions are important to have motivated and committed workforce. Currently in the labor market the employees' decision is affected not only by the wage and career opportunities, but also by the working environment and the operational view of the company. We developed an evaluation criteria system for assessing work and environmental culture. In this paper, the results of the measurements are presented that were conducted among the employees of a big corporation.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.